Baseline Characteristics of Patients With Heart Failure and Preserved Ejection Fraction in the PARAGON-HF Trial - Solomon, Scott D; Rizkala, Adel R; Lefkowitz, Martin P; Shi, Victor C; Gong, JianJian; Anavekar, Nagesh; Anker, Stefan D; Arango, Juan L; Arenas, Jose L; Atar, Dan; Ben-Gal, Turia; Boytsov, Sergey A; et al. (Circulation. Heart failure, 2018)
BACKGROUND: To describe the baseline characteristics of patients with heart failure and preserved left ventricular ejection fraction enrolled in the PARAGON-HF trial (Prospective Comparison of Angiotensin Receptor Neprilysin Inhibitor With Angiotensin Receptor Blocker Global Outcomes in HFpEF) comparing sacubitril/valsartan to valsartan in reducing morbidity and mortality. METHODS AND RESULTS: We report key demographic, clinical, and laboratory findings, and baseline therapies, of 4822 patients randomized in PARAGON-HF, grouped by factors that influence criteria for study inclusion. We further compared baseline characteristics of patients enrolled in PARAGON-HF with those patients enrolled in other recent trials of heart failure with preserved ejection fraction (HFpEF). Among patients enrolled from various regions (16% Asia-Pacific, 37% Central Europe, 7% Latin America, 12% North America, 28% Western Europe), the mean age of patients enrolled in PARAGON-HF was 72.7±8.4 years, 52% of patients were female, and mean left ventricular ejection fraction was 57.5%, similar to other trials of HFpEF. Most patients were in New York Heart Association class II, and 38% had ≥1 hospitalizations for heart failure within the previous 9 months. Diabetes mellitus (43%) and chronic kidney disease (47%) were more prevalent than in previous trials of HFpEF. Many patients were prescribed angiotensin-converting enzyme inhibitors or angiotensin receptor blockers (85%), β-blockers (80%), calcium channel blockers (36%), and mineralocorticoid receptor antagonists (24%). As specified in the protocol, virtually all patients were on diuretics, had elevated plasma concentrations of N-terminal pro-B-type natriuretic peptide (median, 911 pg/mL; interquartile range, 464-1610), and structural heart disease. CONCLUSIONS: PARAGON-HF represents a contemporary group of patients with HFpEF with similar age and sex distribution compared with prior HFpEF trials but higher prevalence of comorbidities. These findings provide insights into the impact of inclusion criteria on, and regional variation in, HFpEF patient characteristics. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifier: NCT01920711.
Keywords: srdeční selhání; Aged; Aged, 80 and over; lidé středního věku; senioři; antagonisté mineralokortikoidních receptorů; blokátory receptorů AT1 pro angiotensin II; antagonisté receptorů pro angiotenzin; Heart Failure; klinické zkoušky jako téma; lidé; Mineralocorticoid Receptor Antagonists; Ventricular Function, Left; Middle Aged; Clinical Trials as Topic; valsartan; inhibitory ACE; Adrenergic beta-Antagonists; Female; beta blokátory; senioři nad 80 let; tepový objem; Angiotensin-Converting Enzyme Inhibitors; Male; ženské pohlaví; Humans; funkce levé komory srdeční; mužské pohlaví; Stroke Volume; Angiotensin Receptor Antagonists; Valsartan; Angiotensin II Type 1 Receptor Blockers